2018
DOI: 10.1016/j.jtcvs.2018.03.147
|View full text |Cite
|
Sign up to set email alerts
|

Robotic mitral valve operations by experienced surgeons are cost-neutral and durable at 1 year

Abstract: Experienced mitral surgeons can initiate a robotic program in a cost-neutral manner that maintains clinical outcome integrity as well as repair durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…Coyan et al should be congratulated for the excellent outcomes of their RMVS cohort and their meticulous analysis of the direct, semidirect, and indirect costs for their large series The Journal of Thoracic and Cardiovascular Surgery c September 2018 ADULT: MITRAL VALVE: EDITORIAL ADULT of patients. 6 This study should provide further support to expand RMVS. As young surgeons seek to develop expertise in this complex technology, studies such as these should continue to provide a benchmark for excellent outcomes.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Coyan et al should be congratulated for the excellent outcomes of their RMVS cohort and their meticulous analysis of the direct, semidirect, and indirect costs for their large series The Journal of Thoracic and Cardiovascular Surgery c September 2018 ADULT: MITRAL VALVE: EDITORIAL ADULT of patients. 6 This study should provide further support to expand RMVS. As young surgeons seek to develop expertise in this complex technology, studies such as these should continue to provide a benchmark for excellent outcomes.…”
mentioning
confidence: 67%
“…5 In this issue of The Journal of Thoracic and Cardiovascular Surgery, the report entitled, ''Robotic mitral valve operations by experienced surgeons are cost-neutral and durable at 1 year,'' is on a progressive study in keeping with the technological advances in cardiac surgery. 6 The authors, Coyan et al, should be commended for their efforts to systematically evaluate the merits of robotic technology as it becomes more widespread and integrated into cardiovascular programs worldwide. 6 Coyan et al 6 focus their study on comparing the cost of robotic mitral surgeries with those using traditional sternotomy (SMVS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors 1 determined that minimally invasive MV surgeries performed with peripheral perfusion were cost-neutral to sternotomy, matching observations from other recent institutional and multi-institutional experiences. [2][3][4] Cost, price, and value; how do we reconcile these elements when evaluating the effectiveness of innovation in thoracic surgery? Value is net patient contribution (quality þ outcomes/cost) and cost-effectiveness attempts to balance the multitude of related factors when comparing alternate therapies.…”
Section: Vinay Badhwar MDmentioning
confidence: 99%
“…8 Durable repair rates for degenerative MV disease and low surgical mortality and major morbidity rates must remain stable or improved as we innovate. As Hawkins et al 1 and others [2][3][4] have shown, adoption of minimally invasive approaches to MV repair or MV replacement is an example of innovation that can be performed with equal cost while maintaining and perhaps enhancing patient outcomes.…”
Section: Vinay Badhwar MDmentioning
confidence: 99%